Hydrogen Storage: The Inside‐Outs of Metal Hydride Dehydrogenation: Imaging the Phase Evolution of the Li‐N‐H Hydrogen Storage System (Adv. Mater. Interfaces 7/2020). Issue 7 (14th April 2020) - White, James L.; Baker, Alexander A.; Marcus, Matthew A.; Snider, Jonathan L.; Wang, Timothy C.; Lee, Jonathan R. I.; Kilcoyne, David A. L.; Allendorf, Mark D.; Stavila, Vitalie; El Gabaly, Farid
Abstract : Hydrogen absorption and release in lithium amide involves chemical and structural change. Scanning transmission X‐ray microscopy visualizes this phase evolution inside particles, showing a core‐shell architecture, with the more hydrogenated species as the shell for hydrogenation and, more surprisingly, for dehydrogenation as well. More details can be found in article number 1901905 by James White, Farid El Gabaly, and co‐workers.